Early caregiving stress exposure moderates the relation between respiratory sinus arrhythmia reactivity at 1 month and biobehavioral outcomes at age 3. (January 2016) - Conradt, Elisabeth; Beauchaine, Theodore; Abar, Beau; Lagasse, Linda; Shankaran, Seetha; Bada, Henrietta; Bauer, Charles; Whitaker, Toni; Hammond, Jane; Lester, Barry
Abstract: There is a growing scientific interest in the psychophysiological functioning of children living in low‐socioeconomic status (SES) contexts, though this research is complicated by knowledge that physiology–behavior relations often operate differently in these environments among adults. Importantly, such research is made more difficult because SES may be a proxy for a wide range of risk factors including poor caregiving and exposure to parental substance use. We used factor analysis to organize risk‐exposure data collected from 827 children—many of whom were raised in low‐SES contexts and exposed to substances prenatally—into dissociable components including economic stress, caregiving stress (e.g., stress the caregiver may experience, including parental psychopathology), and postnatal substance exposure. These factors, along with respiratory sinus arrhythmia (RSA) reactivity at age 1 month, were used to predict behavior dysregulation and resting RSA at age 3 years. A significant RSA Reactivity × Caregiving Stress interaction indicated that infants who exhibited high RSA reactivity at 1 month experienced the greatest behavior dysregulation at 3 years, but only when they were exposed to high levels of caregiving stress. Among African Americans, the highest resting RSA at 3 years was found in infants with less RSA reactivity, but only if they also experienced less caregiving stress. Our work is consistent with biological sensitivity to context, adaptive calibration, and allostatic load models, and highlights the importance of studying Physiology × Environment interactions in low‐SES contexts for predicting behavior and resting RSA.